Haemophagocytic Lymphohistiocytosis Associated with Dengue Fever - A case series (Journal of Medicine, 2020)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening medical condition characterized by hyperphagocytosis secondary to an inappropriate over-activation of macrophages and lymphocytes that driven by excessive cytokines production which resulted in cellular destructions. Dengue induced hemophagocytic lymphohistiocytosis (HLH) is a serious condition and may prove fatal if not detected early and treated appropriately. Diagnosis of HLH is challenging and usually missed as clinical and laboratory findings are nonspecific. It should be suspected with prolonged fever beyond seven days associated with splenomegaly, hyperferritinemia, worsening cytopenias and development of multiorgan dysfunction. A proportion of patients recovered with supportive therapy, however most required interventions with corticosteroids, intravenous immunoglobulin or chemotherapy. We report 3 cases of dengue associated HLH . Among them 2 patients were treated with steroid with good outcome, and one died from MODS.J MEDICINE JUL 2020; 21 (2) : 123-126